(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
"Clinical Anatomy of the Breast: Layers, Cell Spaces, Intercostal Spaces, Topography of the Mammary Gland, and Diaphragm" embarks on a detailed exploration of the anatomical complexities that define the clinical landscape of the breast. This comprehensive study delves into the layers and cell spaces, elucidates the topography of the mammary gland, and establishes the intricate interplay between the breast and diaphragm. The synthesis of clinical and anatomical insights in this study provides a foundational understanding essential for medical practitioners, educators, and researchers in the field